Are sensory phenomena present in Sydenham's Chorea? Evaluation of 13 cases - (:unkn) unknown (GEORG THIEME VERLAG KG, 2004)
Sydenham's Chorea (SC) is an early complication of rheumatic fever caused by group A beta-hemolytic streptococcal infection that manifests itself with adventitious choreatic movements and behavioral problems. Sensory phenomena are the premonitory sensory experiences that are described prior to tics. Tic disorders and SC share common underlying neurobiological substrates, yet sensory phenomena have not previously been examined in SC. We aimed to explore the presence of sensory phenomena associated with choreatic movements in children with SC. Thirteen SC patients are examined on measures of sensory phenomena using a semi-structured instrument. 10 out of 13 patients described sensory phenomena. Five of the SC patients described sensory phenomena as between physical and mental. The patients described physical feelings of tension in joints, tingling and trembling sensations on skin. 69% of them described movements as completely involuntary. Sites of choreatic movements that were consistently preceded by sensory phenomena were upper and lower extremities, and trunk. Children may have difficulty in articulating sensory phenomena due to the subjective nature of premonitory feelings in SC. We recommend exploring the sensory experiences that might accompany the choreatic movements in children with SC.
Keywords: Sydenham's Chorea; sensory phenomena; basal ganglia-related disorders; neuropsychiatric; child; OBSESSIVE-COMPULSIVE DISORDER; TOURETTES-SYNDROME; TICS; SYMPTOMS